The Influence of Organizational Commitment, Competency, Work Motivation and Organizational Culture on Job Satisfaction and Its Impact on The Performance of Aceh Mineral Resources Energy Staff - Hamzali, Said (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to determine the effect of organizational commitment, competence, work motivation and organizational culture on job satisfaction and its impact on the performance of employees of the Aceh Office of Energy and Mineral Resources. The sample in this study was taken using a data collection method called the saturated sampling technique (census). The number of samples used was 117 respondents. Primary data collection is done by distributing questionnaires. The data analysis technique used in this study is The Structural Equation Modeling (SEM) from the AMOS statistical software package for hypothesis testing. The results showed that descriptively organizational commitment, competence, work motivation, organizational culture, job satisfaction and employee performance had gone well. Then the test results directly show that: 1) organizational commitment does not have a significant effect on job satisfaction, 2) competence has a significant effect on job satisfaction, 3) work motivation does not have a significant effect on job satisfaction, 4) organizational culture has a significant effect on job satisfaction, 5) job satisfaction has no significant effect on performance employees, 6) organizational commitment has a significant effect on employee performance, 7) competence does not have a significant effect on employee performance, 8) work motivation does not have a significant effect on employee performance, 9) Organizational culture has a significant effect on the performance of Aceh Department of Energy and Mineral Resources staff. Then the results of this study found that the results of indirect testing of competence had a significant effect on employee performance through job satisfaction at the Aceh Department of Energy and Mineral Resources (partially mediator).